LOCAL DEMOCRACY IN INDONESIA: A COMPARISON OF DIRECT AND INDIRECT REGIONAL HEAD ELECTION SYSTEMS - Muhammad Gaus; Farhanuddin; Muhammad; Asriani; Rahmatullah (PT. Radja Intercontinental Publishing, 2026)
This paper begins with the debate over direct and indirect elections in regional head elections in Indonesia. This study aims to compare the two electoral systems that have each been implemented in Indonesia, particularly in selecting leaders at the regional government level. The research method used is a qualitative descriptive approach , with the primary data source coming from a literature review of scientific journals, books, reports, official documents, and other relevant references. The results show that both systems have a legitimate basis to justify their adherence to democratic values. Ultimately, no system is perfect; the most important thing is to pursue the best strategy within whichever system is agreed upon.